2012
DOI: 10.1002/anie.201205332
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Assisted Photonic Inversion of Supramolecular Handedness

Abstract: Spiraling into control: A photoresponsive supramolecular assembly demonstrates that light, along with heating (Δ) and cooling (), can cause chiral communication between molecules. This effect leads to bias in the helicity of the complex, causing a reversible switching of macroscopic handedness, as shown by a reversal of sign of the circularly polarized luminescence (CPL) that is emitted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
97
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(100 citation statements)
references
References 76 publications
0
97
0
3
Order By: Relevance
“…Exposure of the fiber to chiral analytes capable of hydrogen bonding with gelator 1 facilitates stabilization of the twisted stacking arrangement of gelator 1, thereby yielding the helical form of the fiber. 20 The azobenzene moiety, in general, has been widely used as a component for a diverse range of applications, such as photoresponsive supramolecular systems. The non-helical fiber at this point can again be transformed into a helical configuration by addition of a particular analyte that may again stabilize the twisted stacking arrangement by hydrogen bonding with gelator 1.…”
Section: Resultsmentioning
confidence: 99%
“…Exposure of the fiber to chiral analytes capable of hydrogen bonding with gelator 1 facilitates stabilization of the twisted stacking arrangement of gelator 1, thereby yielding the helical form of the fiber. 20 The azobenzene moiety, in general, has been widely used as a component for a diverse range of applications, such as photoresponsive supramolecular systems. The non-helical fiber at this point can again be transformed into a helical configuration by addition of a particular analyte that may again stabilize the twisted stacking arrangement by hydrogen bonding with gelator 1.…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11]13,14 It has been also shown that OPEs are able to selforganize into microcrystalline lamellae 20 or into micrometric-size associates 21 as well as to amplify chirality 22 or to invert supramolecular handedness. 23 Furthermore, a recent study confirmed that the interchain π-interactions in OPEs have strong impact on the photophysical properties of the self-assembled materials. 24 Pyridine-centered tridentate ligands are highly versatile building blocks that are extensively used in coordination chemistry.…”
Section: -7mentioning
confidence: 90%
“…7a) [13]. In the (E,E) forms before isomerization, (S)-and (R)-9, which formed aggregates in methylcyclohexane (1 × 10 -4 M), showed positive and negative CPL with g lum values of +0.008 and -0.01, respectively, at 503 nm (Fig.…”
Section: Stimuli-responsive Cpl Properties Of -Conjugated Moleculesmentioning
confidence: 92%
“…The CPL observed in this study is associated with the respective helicity of the assembled structures. The result suggested that the assembly of the (E,E) form alone and that consisting of all the isomers exhibited opposite chirality [13].…”
Section: Stimuli-responsive Cpl Properties Of -Conjugated Moleculesmentioning
confidence: 97%